The Risk of Contact Lens Wear and the Avoidance of Complications - Farihah Tariq; Peter Koay (University Library System, University of Pittsburgh, 2013)
Contact lenses are lenses placed on the surface of the cornea to correct refractive errors such as myopia (short-sightedness), hypermetropia (far-sightedness) and astigmatism. Lens-related complications are becoming a greater health concern as increasing number of individuals are using them as an alternative to spectacles. Contact lenses alter the natural ocular environment and reduce the efficacy of the innate defences. Although many complications are minor, microbial keratitis is potentially blinding and suspected cases should be rapidly diagnosed and referred to an ophthalmologist for treatment. Several risk factors have been identified with extended wear, poor hand hygiene, inadequate lens and lens-case care being the most significant. Promotion of good contact lens hygiene and practices are essential to reduce the adverse effects of contact lens wear.